Probiotic and functional potential of lactic acid bacteria isolated from pulque and evaluation of their safety for food applications - Ruiz-Ramírez, Yesica; Valadez-Blanco, Rogelio; Calderón-García, Concepción; Chikindas, Michael Leonidas; Ponce-Alquicira, Edith (Frontiers in Microbiology, 2023)
Pulque is a traditional Mexican non-distilled alcoholic beverage to which several beneficial functions are attributed, mainly associated with gastrointestinal health, which can be explained by the presence of probiotic bacteria in its microbiota. Therefore, the objective of this work was to evaluate the safety, probiotic activity, and functional characteristics of seven strains of lactic acid bacteria (LAB) isolated from pulque using the probiotic strain Lactobacillus acidophilus NCFM as control. The LAB isolates were identified by 16S rRNA sequencing and MALDI Biotyper® MS as belonging to three different Lactobacillaceae genera and species: Lactiplantibacillus plantarum, Levilactobacillus brevis and Lacticaseibacillus paracasei. Most strains showed resistance to gastric juice, intestinal juice and lysozyme (10 mg/L). In addition, all strains exhibited bile salt hydrolase (BSH) activity and antibacterial activity against the pathogenic strain Listeria monocytogenes. Additionally, cell surface characteristics of LAB were evaluated, with most strains showing good hydrophobicity, auto-aggregation, and co-aggregation towards enteropathogenic Escherichia coli and L. monocytogenes. In terms of safety, most of the strains were sensitive to the tested antibiotics and only the Lact. paracasei UTMB4 strain amplified a gene related to antibiotic resistance (mecA). The strains Lact. plantarum RVG2 and Lact. plantarum UTMB1 presented γ-hemolytic activity, and the presence of the virulence-related gene agg was identified only in UTMB1 strain. Regarding functional characterization, the tested bacteria showed good β-galactosidase activity, antioxidant activity and cholesterol reduction Based on principal component analysis (PCA) and heat mapping, and considering the strain Lact. acidophilus NCFM as the probiotic reference, the strains Lacticaseibacillus paracasei UTMB4, Lactiplantibacillus plantarum RVG4 and Levilactobacillus brevis UTMB2 were selected as the most promising probiotic strains. The results of this study highlighted the probiotic, functional and safety traits of LAB strains isolated from pulque thus supporting the health benefits attributed to this ancestral beverage.